Prevalência de disfunção sexual em estudantes universitárias fisicamente ativas: estudo caso-controle - Rosseto, Patricia Pelegrina [UNIFESP] (2020)
Introduction: A woman’s sexual life may have influence from several factor like the sexual dysfunctions. The maintenance of female’s health may be favored by the physical activity making illnesses’ prevention possible. Physical activity may affect the self-image influencing the experience of sexuality. Aim: investigate the prevalence of sexual dysfunctions in college female students physically active in comparison to sedentary one. Methods: Transversal study, like case-control, accomplished through electronic and printed quiz. Female college students ranging from 18 to 40 years of age took part in this research. The case group consisted of female college students who had regular physical activity and the control group consisted of sedentary female college students, in the same age range. The sexual function was evaluated through Female Sexual Function Index – FSFI. Results: 202 female college students were evaluated, among them 22 sedentary ones and 180 active ones. The sexual dysfunction was more prevalent in the sedentary group (45,5%) when compared to the physically active group (38,9%) (p=0,646), however without statistical significance. In relation to the subjects evaluated by the FSFI, only the “arousal” subject presented statistically significant difference. (p=0,031). Conclusion: The prevalence of sexual dysfunction in active and sedentary female college students was similar, without association between sexual dysfunction and physical activity.